17 Lyme Disease in Eastern Ontario - A Paediatric Centre's Experience from 2009-2018. (19th August 2020) - Zahradnik, Stephanie; Barrowman, Nick; Tsampalieros, Anne; Harrison, Mary-Ann; Bowes, Jennifer; Brophy, Jason
Abstract: Background: Lyme disease (LD) is caused by the tick-borne bacterium Borrelia burgdorferi . Over the past ten years, robust local public health data indicates that the incidence of LD has increased significantly in the eastern region of Ontario due to the spread of its vector, the blacklegged tick. As a result, we have seen an increase in the number of cases of LD in children at our tertiary paediatric centre, at all stages of infection. Familiarity with Lyme disease is important as incidence increases. We sought to characterize the cases at our centre. Objectives: To describe the epidemiology of LD in children at our centre from 2009-2018, as well as the variety of clinical presentations of paediatric LD. Design/Methods: We completed a retrospective chart review from 2009-2018 of all cases admitted or seen in the Infectious Disease (ID) clinic or the Emergency Department (ED) with a diagnosis of LD. Demographic, clinical and laboratory data were collected, including geographic location where infection occurred and resource utilization. We used descriptive statistics to describe cases and comparative statistics to determine changes in number of cases over time. Results: There were 171 LD cases managed at our centre during this period. Mean age was 7.4 (SD 4.5) years, 89 (52.0%) were male. The annual number of cases from 2009 - 2018 increased from 1 to 44 and peaked in 2017 (47 cases). The highest number of cases occurred among children <6, the lowest in children ≥11. Most cases occurred in summer (60%), with the fewest in winter months (4%). Stage of LD was not documented in 1 case. Of the remainder, 98 (57.6%) cases were early localized, 41 (25.7%) early disseminated and 31 (19.7%) late disseminated LD. Early and late disseminated cases occurred more commonly in the summer and accounted for the majority of admissions. These included neurologic Lyme (lymphocytic meningitis [2, 1.2%], polyneuropathy [1, 0.6%], cranial nerve palsy [13, 7.6%]), Lyme carditis (5, 2.9%), and Lyme arthritis (29, 17.0%). There were 133 (77.8%) patients managed in ED, 66 (38.6%) in the ID clinic and 17 (9.9%) in the inpatient ward; median length of stay was 6 (IQR 5, 9) days, with a range of 1 to 30 days. The most common geographic locations of infection acquisition were Ottawa (120 cases, 71.0%) and Kingston (26, 15.4%). Conclusion: Cases of LD managed at our paediatric centre have increased in keeping with population trends, with all LD stages experienced. Severe cases of meningitis, carditis, and arthritis resulted in hospitalization, with increasing numbers over the study period.